2015
DOI: 10.1038/mp.2014.193
|View full text |Cite
|
Sign up to set email alerts
|

X-exome sequencing of 405 unresolved families identifies seven novel intellectual disability genes

Abstract: X-linked intellectual disability (XLID) is a clinically and genetically heterogeneous disorder. During the past two decades in excess of 100 X-chromosome ID genes have been identified. Yet, a large number of families mapping to the X-chromosome remained unresolved suggesting that more XLID genes or loci are yet to be identified. Here, we have investigated 405 unresolved families with XLID. We employed massively parallel sequencing of all X-chromosome exons in the index males. The majority of these males were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
323
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(356 citation statements)
references
References 128 publications
17
323
0
2
Order By: Relevance
“…4 CGG-repeat expansion in the FMR1 promoter is the most frequent cause of FXS, but deletions of the entire FMR1 gene [10][11][12] or of the 5′UTR have also been reported in FXS. 9 Rare intragenic non-synonymous variations have also been identified within the FMR1 locus [16][17][18][19][20]22,23,35,41,42 but after reanalysis in the light of new public sequencing data, prediction tools and functional evidence, we showed that only six could be reclassified as convincing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 CGG-repeat expansion in the FMR1 promoter is the most frequent cause of FXS, but deletions of the entire FMR1 gene [10][11][12] or of the 5′UTR have also been reported in FXS. 9 Rare intragenic non-synonymous variations have also been identified within the FMR1 locus [16][17][18][19][20]22,23,35,41,42 but after reanalysis in the light of new public sequencing data, prediction tools and functional evidence, we showed that only six could be reclassified as convincing.…”
Section: Discussionmentioning
confidence: 99%
“…We have also compiled the rare non-synonymous variants identified in FMR1 during large-scale studies (large panel, X-exome or wholeexome sequencing) performed on ID patients by other teams: only missense variants but no truncating variants were identified in the 3180 individuals tested. [33][34][35][36][37][38][39][40][41][42] We reanalyzed all these variants in FMR1 in the light of new public sequencing data (Exome Variant Server and the ExAC project, supposed to be free or at least not enriched in severe developmental disorders), prediction tools and functional evidence. Altogether, six previously reported variants could also be reclassified as disease-causing (pathogenic-class 5 or likely pathogenic-class 4 variants, summarized in Table 3 and in Figure 4).…”
Section: Identification Of Two Novel Intronic Variants Affecting Fmr1mentioning
confidence: 99%
“…The effect was particularly marked with the c.119T>A (p.Met40Lys) variant. In addition to these clinical, genetic, modeling, and biochemical results, the fact that mutations in other components of the TFIID complex (TAF1, TAF2, TAF6, and TBP) lead to a neurological phenotype [8][9][10][11][12][13][14][15] strongly supports our hypothesis that bi-allelic pathogenic alterations in the histone fold domain of TAF13 lead to mild ID and microcephaly. TAF13 is a constituent of at least two protein complexes: the TFIID complex and the small nuclear RNA genespecific TAF complex (snTAFc), which play a critical role in the regulation of gene transcription in eukaryotic cells.…”
mentioning
confidence: 51%
“…Intriguingly, in other subunits of TFIID, different variants lead to different phenotypes. Variants in TAF1 are associated with ID and microcephaly 13,14 whereas the reduction in TAF1 expression is associated with XDP 10 (Table S1). Also, in TBP, the expansion of the polyglutamine (polyQ) tract causes SCA17 probably in a gain-of-function mode, whereas heterozygous deletion of TBP is probably responsible for ID and microcephaly 9,29 (Table S1).…”
mentioning
confidence: 99%
“…There are still many likely X-linked cases in which there is no molecular diagnosis. Hu et al (2015) performed a study on 405 families, which had clear familial evidence of XLID. These families were termed unresolved because despite microarray-based copy number variation (CNV) analysis and Sanger sequencing of a subset of XLID genes there was no definitive cause of ID.…”
Section: Chromosome -Targeted Sequencing Studiesmentioning
confidence: 99%